The within-distribution business cycle dynamics of German firms - Sebastian Weber; Jörg Döpke (Deutsche Bundesbank, 2006)
We analyse stylised facts for Germany's business cycle at the firm level. Based on longitudinal firm-level data from the Bundesbank's balance sheet statistics covering, on average, 55,000 firms per year from 1971 to 1998, we estimate transition probabilities of a firm in a certain real sales growth regime switching to another regime in the next period, e.g. whether a firm that has witnessed a high growth rate is likely to stay in a regime of high growth or is bound to switch in a regime of low growth in the subsequent period. We find that these probabilities depend on the business cycle position.
Keywords: D21; D92; E32; 330; business cycles; firm growth; Markov chains; Unternehmensentwicklung; Unternehmenswachstum; Konjunktur; Markovscher Prozess; Schätzung; Deutschland